2018
DOI: 10.1017/s1751731117002257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-weaning housing in a multi-suckling system on performance and carbohydrate absorption of relatively light and heavy piglets around weaning

Abstract: The low feed intake and stress associated with abrupt weaning in conventional pig farming often result in poor post-weaning performance, which is related to impaired intestinal function. We investigated effects of housing conditions before weaning on performance around weaning of relatively light and heavy piglets. Before weaning, piglets were housed either with five sows and their litters in a multi-suckling (MS) system or in pens with individually housed sows in farrowing crates (FC). After weaning at 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A possible explanation could be that the piglets might cope better with social stress at weaning, resulting in a reduction of stressors which in turn positively affects gut health by a better utilisation of feed and consequently performance of the piglets in the early postweaning period. Recent research of van Nieuwamerongen et al (2018) highlighted the impact of pre-weaning housing conditions such as co-mingling non-littermates in a multi-suckling system on intestinal function in piglets immediately after weaning, evidenced by a better feed conversion between day 2 and 5 post-weaning and differences in gastrointestinal carbohydrate absorption. Moreover, lower prevalence of aggressive behaviour is associated with a better feed conversion ratio in piglets (Pierozan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be that the piglets might cope better with social stress at weaning, resulting in a reduction of stressors which in turn positively affects gut health by a better utilisation of feed and consequently performance of the piglets in the early postweaning period. Recent research of van Nieuwamerongen et al (2018) highlighted the impact of pre-weaning housing conditions such as co-mingling non-littermates in a multi-suckling system on intestinal function in piglets immediately after weaning, evidenced by a better feed conversion between day 2 and 5 post-weaning and differences in gastrointestinal carbohydrate absorption. Moreover, lower prevalence of aggressive behaviour is associated with a better feed conversion ratio in piglets (Pierozan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced feed intake after weaning is variable from 24 h to 4 d depending of individuals [ 14 ] and has been reported to be the most important factor compromising intestinal barrier function ahead of dietary change [ 15 ]. The lack of nutrients in the intestine of piglets may contribute to intestinal inflammation and changes in intestinal morphology such as reduced villus height and increased intestinal permeability which facilitate the crossing of the mucus layer and the intestinal epithelial barrier by toxins and bacteria [ 3 , 12 , 16 ]. This mucus layer is a permeable gel overlying intestinal epithelial cells, separating them from gut luminal content, including commensal bacteria and invading pathogens [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment by Rantzer et al (1997) [122], in which a multi-suckling system was compared with a conventional housing system, the average diarrhea score did not differ after weaning, despite the fact that the peak excretion of hemolytic E. coli was delayed in piglets from the multi-suckling system. The fecal consistency scores after weaning also did not differ between pigs reared in a multi-litter system and a conventional system in the study of van Nieuwamerongen et al (2018) [124]. However, in the study, lower plasma sugar concentrations such as mannitol and galactose were observed on day 5 after weaning in pigs raised in the multi-litter system.…”
Section: Effects Of Co-mingling Before Weaning On Mortality Before An...mentioning
confidence: 55%